Engineering Nicotiana benthamiana for chrysoeriol production using synthetic biology approaches - Lee, Saet Buyl; Lee, Sung-eun; Lee, Hyo; Kim, Ji-Su; Choi, Hyoseon; Lee, Sichul; Kim, Beom-Gi (Frontiers in Plant Science, 2024)
Flavonoids are prevalent plant secondary metabolites with a broad range of biological activities. Their antioxidant, anti-inflammatory, and anti-cancer activities make flavonoids widely useful in a variety of industries, including the pharmaceutical and health food industries. However, many flavonoids occur at only low concentrations in plants, and they are difficult to synthesize chemically due to their structural complexity. To address these difficulties, new technologies have been employed to enhance the production of flavonoids in vivo. In this study, we used synthetic biology techniques to produce the methylated flavone chrysoeriol in Nicotiana benthamiana leaves. The chrysoeriol biosynthetic pathway consists of eight catalytic steps. However, using an Agrobacterium-mediated transient expression assay to examine the in planta activities of genes of interest, we shortened this pathway to four steps catalyzed by five enzymes. Co-expression of these five enzymes in N. benthamiana leaves resulted in de novo chrysoeriol production. Chrysoeriol production was unaffected by the Agrobacterium cell density used for agroinfiltration and increased over time, peaking at 10 days after infiltration. Chrysoeriol accumulation in agroinfiltrated N. benthamiana leaves was associated with increased antioxidant activity, a typical property of flavones. Taken together, our results demonstrate that synthetic biology represents a practical method for engineering plants to produce substantial amounts of flavonoids and flavonoid derivatives without the need for exogenous substrates.